KEWENANGAN DEWAN PERWAKILAN RAKYAT DAERAH DALAM MENETAPKAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH - Angga Tonny Mashita, Gede; Atmadja, I Dewa Gede (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014)
The Regional Government sent the Regional Budgeting Plan to the Regional Assembly annually. The suggestion is accompanied by the needed budget allocation. The function of the regional assembly is the estimation function that conducts by the regional legislator efficiently and effectively. with the problems; how is the regional assembly’s authority in deciding the Regional Budgeting Plan that is sent by the governor, and what is the law effect of the ignored regional Budgeting Plan that is sent by the governor. This research is normative legal research. The obtained conclusion is that Regional Assembly has an authority to give agreement of determination and it can ignore the suggestion of the Regional Budgeting Plan through the factions in the Regional Assembly. And if regional budgeting cannot be realized as the obtained certainty, it will has legal cause to the regional budgeting determination which influences to the regional development.
Keywords: Regional Government, Regional Assembly, legislator, Authority